2021
DOI: 10.3892/mmr.2021.12174
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid alleviates lipopolysaccharide‑induced H9C2 cell apoptosis by suppressing reactive oxygen species‑mediated endoplasmic reticulum stress

Abstract: Sepsis-induced myocardial dysfunction is one of the features of multiple organ dysfunction in sepsis, which is associated with extremely high mortality and is characterized by impaired myocardial compliance. To date, there are few effective treatment options available to cure sepsis. Tannic acid (TA) is reportedly protective during sepsis; however, the underlying mechanisms by which TA protects against septic heart injury remain elusive. The present study investigated the potential effects and underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…TA treatment reduced apoptosis, as evidenced by favorable modulation of Bcl-2, Bax, and cytochrome-C. Previously, it was demonstrated that ROS inhibition considerably suppress the expressions of apoptotic proteins [ 59 ], and thus, TA, as a potent antioxidant, invoked its neuroprotective actions through its potent free radical scavenging and antioxidant properties.…”
Section: Discussionmentioning
confidence: 98%
“…TA treatment reduced apoptosis, as evidenced by favorable modulation of Bcl-2, Bax, and cytochrome-C. Previously, it was demonstrated that ROS inhibition considerably suppress the expressions of apoptotic proteins [ 59 ], and thus, TA, as a potent antioxidant, invoked its neuroprotective actions through its potent free radical scavenging and antioxidant properties.…”
Section: Discussionmentioning
confidence: 98%
“…The impact of TA on many oncological signal pathways, including VEGF/VEGFR, RAS/RAF/mTOR, JAK/STAT, TGF-β1R/TGF-β1R axis, and CXCL12/CXCCR4 axes, has been seen. TA can initiate endoplasmic reticulum (ER) stress through the unfolded protein response (UPR) pathway, leading to the activation of apoptosis as a potential strategy for cancer treatment ( Yang et al, 2021 ). Cell death and apoptosis in cancer cells are accelerated by ER stress [70], as ER is responsible for critical processes, including protein synthesis, maturation, folding, and transport ( Lemmer et al, 2021 ).…”
Section: Mechanisms Of Action In Cancer Cellsmentioning
confidence: 99%
“…These disease models include neuroinflammation, colitis, depressive‐like behaviors, acute lung injury, and septic heart injury (Kawano et al, 2020; Luduvico et al, 2020; Sivanantham, Pattarayan, Rajasekar, et al, 2019). In vitro studies also suggested that HT mainly alleviated inflammatory response by reducing the inflammatory cytokines and inhibiting ROS production in cells (Wu et al, 2019; Yang et al, 2021). These research indicated that the anti‐inflammatory activity of HT were primarily correlated to the antioxidant ability to eliminate free radicals and suppress the expression of proinflammatory cytokines.…”
Section: Hydrolysable Tanninsmentioning
confidence: 99%